IoT-based Clothesline Monitoring and Control System Design with Smartphone Display - Rena Ramadhani Putri; Pakhrur Razi (Georest, 2024)
Indonesia is geographically located on the equator and has two seasons: the rainy season and the dry season. The current global warming has made the weather erratic, making the dry and rainy seasons unpredictable. This is a problem for people who want to dry clothes. To overcome this problem, an automatic control system is needed that can be monitored remotely via Smartphone. This research, with the title Designing an Automatic Clothesline Tool Based on the Internet Of Things, this tool is designed as an automatic control system for clothespins that can be monitored via smartphone remotely, so people don't have to worry about leaving the clothesline. This tool uses NodeMCU Esp32 and uses a rain sensor to detect weather conditions. DC motor is used to move the clothesline in or clothesline out which is controlled by a motor driver. Limit Switch to provide feedback that the clothesline has entered or the clothesline is out.